An almost Cubic Lower Bound for Depth Three Arithmetic Circuits - Kayal, Neeraj; Saha, Chandan; Tavenas, Sébastien (ICALP 2016, 2016)
We show an almost cubic lower bound on the size of any depth three arithmetic circuit computing an explicit multilinear polynomial in n variables over any field. This improves upon the previously known quadratic lower bound by Shpilka and Wigderson [CCC, 1999].